ANALISIS PENGGUNAAN MATA UANG ASING DALAM PERJANJIAN JUAL BELI DI INDONESIA BERDASARKAN SYARAT SAH PERJANJIAN - Ivanov, Irsandi; Lestari, Rika; Dasrol, Dasrol (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2024)
The case of people in border areas who still use payment transactions in foreigncurrency is the people of Nunukan Regency, North Kalimantan, specifically the peopleof Krayan District, which borders Sarawak, Malaysia. Nunukan Regency is located inthe northernmost region of North Kalimantan Province. This district borders directlywith the state of Sabah (East Malaysia) to the north, with Bulungan and Malinaudistricts to the south, to the south with the state of Sarawak (East Malaysia) and to theeast with the Sulawesi Sea. Nunukan Regency, which was inaugurated as anautonomous region in 1999, occupies an area of 14,247.50 km2. The applicablecurrency is not only Rupiah, it also uses Ringgit.The type of research used is normative research on legal principles, namely theprinciple of legal certainty, so research on legal principles is carried out on legal rules,which are standards for inappropriate behavior or behavior. This research can becarried out on primary and secondary legal materials. The data sources used in thisresearch are secondary data, namely data obtained from literature studies and havebinding legal force, consisting of primary legal materials, secondary legal materialsand tertiary legal materials. The data collection technique used by the author in thisresearch is using library research, namely researching reading sources related to thetopic in this research such as: law books, statutory regulations, court decisions relatedto research, opinions of scholars and other supporting materials.Based on the results of the research and discussion, it can be explained asfollows: First, the validity of buying and selling using foreign currency in Indonesianterritory is based on the legal conditions of the agreement, violating the legalconditions of the agreement contained in Article 1320 of the Civil Code, namely notfulfilling halal reasons. That by using foreign currency, it means violating Law Number7 of 2011 concerning Currency. Second, The impact of the use of foreign currency onsociety in Indonesia can be summarized into several parts, namely: Legal impact:Imprisonment for a maximum of 1 (one) year and a maximum fine of IDR200,000,000.00. The civil legal impact is that because the principal of the agreementand the legal conditions are not in accordance with statutory regulations, theagreement made by the people of the border area is considered null and void. Theimpact from an economic perspective is depreciation of the currency value which makesthe bargaining value of the Rupiah low which can increase the price of local goods andaffect foreign debt payments, which leads to increasingly worse social inequality. Theimpact in terms of domestic security will be crimes that have economic reasons,because the state fails to maintain economic stability.Keywords: Agreement - Currency - Border Areas